Aspergillus-related lung mass masquerading as a lung tumour - Mohamed, Saifullah (J Surg Case Rep, 2020)
Aspergillus is a common environmental pathogen. However, clinically significant disease only occurs in a small proportion of patients. Although rare in its occurrence, it remains a considerable cause of morbidity and mortality in certain cohorts of patients. We describe a rare case of Aspergillus disease masquerading as a primary lung malignancy. Computer tomography pulmonary angiogram scan demonstrated a right upper lobe 8 x 6.5 cm soft-tissue lesion. Positron emission tomography CT demonstrated this lesion to be intensely fluorodeoxyglucose avid. Initial bronchoscopy demonstrated occluded subsegmental right upper lobe bronchus with white friable material. Follow-up bronchoscopy demonstrated evidence of a previous inflammatory process with cavitation and destruction of sub-lobar bronchial tree. Serial chest radiographs demonstrated almost complete resolution of the right upper lobe mass. Thus, this presentation of an Aspergillus-related lung mass masquerading as a primary lung malignancy provided several important learning points pertaining to diagnosis and ensuing management.